Normativity in language and linguistics - Mäkilähde, Aleksi; Leppänen, Ville; Itkonen, Esa (Studies in language companion series ;, 2019)
"This volume sets out to discuss the role of norms and normativity in both language and linguistics from a multiplicity of perspectives. These concepts are centrally important to the philosophy and methodology of linguistics, and their role and nature need to be investigated in detail. The chapters address a range of issues from general questions about ontology, epistemology and methodology to aspects of particular subfields (such as semantics and historical linguistics) or phenomena (such as construal and code-switching). The volume aims to further our understanding of language and linguistics as well as to encourage further discussion on the metatheory of linguistics. Due to the fundamental nature of the issues under discussion, this volume will be of interest to all linguists regardless of their background or fields of expertise and to philosophers concerned with language or other normative domains"--